Imaging laser-induced fragmentation of molecular beams, from positive to negative molecules - Berry, Benjamin (Kansas State University, 2018)
The use of ultrafast lasers allows one to study and even control quantum mechanical systems on their natural timescales. Our aim is to study the fragmentation of small molecules in strong laser fields as a means to gain understanding of molecular dynamics and light-matter interactions. Our research group has utilized fast, positively charged molecular ion beams as targets to study and control fragmentation by strong laser fields. This approach allows for detection of all molecular fragments including neutrals, and a coincidence three-dimensional momentum imaging technique is used to characterize the fragmentation. A natural extension of these types of studies is to expand the types of molecular systems that can be studied, from positively charged molecules to neutral and negatively charged molecules. To that end, the primary technical development of this dissertation involved the generation and use of fast, negatively charged molecular beams. Using fast molecular anion beams as targets allows for the study of fragmentation in which all fragments are neutral. As a demonstration, we employ this capability to study F2- dissociation and photodetachment. The dissociation pathways are identified and used to evaluate the initial vibrational population of the F2- beam. The role of dissociation in photodetachment is also explored, and we find that it competes with other dissociative (F+F) and non-dissociative (F2) photodetachment mechanisms. Also highlighted are studies of fragmentation of LiO-, in which the dissociation into Li+O- fragments provides information about the structure of Li O-, including the bond dissociation energy, which was found to be larger than values based on theory. Studies of the autodetachment lifetimes of Li O- were also performed using a pump-probe technique. Additional experimental advancements have made successful pump-probe studies of the ionization of HD+ and Ar2+ possible. Enhancement in the ionization of dissociating HD+ and Ar2+ was observed at surprisingly large internuclear separation where the fragments are expected to behave like separate atoms. The analysis methods used to quantify this enhancement are also described. Finally, the production of excited Rydberg D* fragments from D2 molecules was studied utilizing a state-selective detection method. The carrier-envelope phase dependence of D* formation was found to depend on the range of excited final states of the atomic fragments. We also measured the excited state population of the D* fragments. Together, the studies presented in this work provide new information about fragmentation of positive, negative, and neutral molecules in strong laser fields, and the experimental developments serve as building blocks for future studies that will lead to a better understanding of molecular dynamics.
Keywords: Strong field physics; Ultrafast laser studies; Molecular ion beams; Momentum imaging; Molecular physics